Opioid Therapy in Cancer Patients and Survivors at Risk of Addiction, Misuse or Complex Dependency - Pergolizzi, Joseph V.; Magnusson, Peter; Christo, Paul J.; LeQuang, Jo Ann; Breve, Frank; Mitchell, Kailyn; Varrassi, Giustino (Frontiers in Pain Research, 2021)
A clinical conundrum can occur when a patient with active opioid use disorder (OUD) or at elevated risk for the condition presents with cancer and related painful symptoms. Despite earlier beliefs that cancer patients were relatively unaffected by opioid misuse, it appears that cancer patients have similar risks as the general population for OUD but are more likely to need and take opioids. Treating such patients requires an individualized approach, informed consent, and a shared decision-making model. Tools exist to help stratify patients for risk of OUD. While improved clinician education in pain control is needed, patients too need to be better informed about the risks and benefits of opioids. Patients may fear pain more than OUD, but opioids are not always the most effective pain reliever for a given patient and some patients do not tolerate or want to take opioids. The association of OUD with mental health disorders (dual diagnosis) can also complicate delivery of care as patients with mental health issues may be less adherent to treatment and may use opioids for “chemical coping” as much as for pain control.